2013
DOI: 10.1523/jneurosci.4989-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

GABABReceptors Regulate Extrasynaptic GABAAReceptors

Abstract: Tonic inhibitory GABA A receptor-mediated currents are observed in numerous cell types in the CNS, including thalamocortical neurons of the ventrobasal thalamus, dentate gyrus granule cells, and cerebellar granule cells. Here we show that in rat brain slices, activation of postsynaptic GABA B receptors enhances the magnitude of the tonic GABA A current recorded in these cell types via a pathway involving G i/o G proteins, adenylate cyclase, and cAMP-dependent protein kinase. Using a combination of pharmacology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 30 publications
(34 reference statements)
7
80
4
Order By: Relevance
“…The exact mechanism of this GABA B R-mediated enhancement of eGABA A R activity is unclear, though it seems to be independent on the synthesis of new channels since a maximal tonic GABA A current augmentation can be achieved within 5-10 min from the application of baclofen. Indeed, by diffusing drugs intracellularly, it could be demonstrated that the signalling pathway is dependent on PKA (Connelly et al 2013) (Fig. 7.1), indicating direct control of eGABA A Rs via phosphorylation, as has been demonstrated in expression systems (Tang et al 2010).…”
Section: Gaba B Rs-egaba a Rs Interactionsupporting
confidence: 52%
See 3 more Smart Citations
“…The exact mechanism of this GABA B R-mediated enhancement of eGABA A R activity is unclear, though it seems to be independent on the synthesis of new channels since a maximal tonic GABA A current augmentation can be achieved within 5-10 min from the application of baclofen. Indeed, by diffusing drugs intracellularly, it could be demonstrated that the signalling pathway is dependent on PKA (Connelly et al 2013) (Fig. 7.1), indicating direct control of eGABA A Rs via phosphorylation, as has been demonstrated in expression systems (Tang et al 2010).…”
Section: Gaba B Rs-egaba a Rs Interactionsupporting
confidence: 52%
“…7.1), indicating direct control of eGABA A Rs via phosphorylation, as has been demonstrated in expression systems (Tang et al 2010). Interestingly, both studies (Connelly et al 2013;Tao et al 2013) reported that a GABA B antagonist reduced the tonic GABA A current even in the absence of activation by a GABA B agonist ( Fig. 7.1), indicating that at least in brain slices ambient GABA levels in thalamus, cerebellum and dentate gyrus are sufficient to activate this GABA B R-eGABA A interaction.…”
Section: Gaba B Rs-egaba a Rs Interactionmentioning
confidence: 52%
See 2 more Smart Citations
“…Of note, the baclofen effect on LICI of the N100 was expressed ipsilateral, whilst the baclofen effect on LICI of the P180 was expressed contralateral to the stimulation. The mechanisms of baclofen-induced enhancement of LICI of these potentials are not clear, but may involve enhanced GABABergic neurotransmission in local inhibitory networks at the site of the stimulation, enhanced local GABABergic control of transcallosal inputs to the contralateral hemisphere (Irlbacher et al, 2007;Palmer et al, 2013), or a cross-talk between GABABRs and GABAARs as recently described within the thalamus (Connelly et al, 2013), resulting in disrupted thalamo-cortical communication important for propagation of later TEPs from the stimulated to the non-stimulated hemisphere.…”
Section: Drug Effects On Licimentioning
confidence: 98%